ACCOUNTING FOR DIVIDENDS. - Sine, Edward P. (The Accounting Review, 1953)
There are two major problems in connection with accounting for corporate dividends. The first of these involves the source of the dividend; the second concerns the form or type of dividend. The American Institute of Accountants has held that the credit item in an upward revaluation should be regarded as part of the capital structure, not available for transfer to retained earnings; the item should be frozen until disposed of, if at all, by means of a stock dividend. In some circumstances, dividends may even be paid out of actual capital. This is legally permissible in the cases of wasting asset dividends, dividends out of reduction surplus or dividends declared during construction. Dividends are most commonly paid in cash, although they also may be paid in property, the company's own securities, securities of other companies held by it as investments or scrip. In other words, the dividend may represent a distribution of corporate assets, the establishment of a corporate liability or merely a transfer between proprietorship accounts. Accounting for the stock dividend is in accordance with the method of allocation determined upon.